Checkpoint inhibitors as treatment for malignant gliomas: "A long way to the top". (September 2018) - Simonelli, Matteo; Persico, Pasquale; Perrino, Matteo; Zucali, Paolo Andrea; Navarria, Pierina; Pessina, Federico; Scorsetti, Marta; Bello, Lorenzo; Santoro, Armando
Highlights: PD-1, CTLA-4, TIM-3 and IDO are the most characterized immune checkpoints in gliomas. PD-L1 expression in gliomas is documented, but its prognostic role remains unclear. Checkpoint blockade induce long-lasting remissions in glioma mouse models. Nivolumab did not prolong survival of recurrent GBM patients compared to bevacizumab. Combinatorial approaches with antiangiogenic therapy and RT seem very promising. Abstract: Glioblastoma is the most common and lethal malignant brain tumor in adults, with a very poor prognosis of less than two years despite surgical resection followed by radiotherapy and chemotherapy. To date, targeted agents and antiangiogenic therapy have failed to show survival benefits and novel treatment approaches are urgently needed. Immune checkpoint inhibitors have recently revolutionized the landscape of cancer immunotherapy achieving regulatory approvals for a number of other 'historically' resistant cancers. These exciting successes have generated great interest in investigating if these agents could be such effective also in brain tumors field. Moreover, the traditional dogma that considers the central nervous system (CNS) as an immune-privileged site lacking the potential for immunosurveillance has been challenged as it has become clear that the CNS is immunoactive. Critical barriers to an effective antitumor immunity in brain tumor patients are still represented by the peculiar CNS immunological milieu and the numerous systemic and local immunosuppressive forces exhibited by malignant gliomas to avoid immune recognition and cellular death. This review describes the current status of checkpoint modulation as treatment for malignant gliomas. We start illustrating the compelling molecular and immunological rationale, than we show striking preclinical evidence of activity and discuss available data from prospective clinical trials. Furthermore, we explore the role of predictive biomarkers of responsiveness to checkpoint blockade in the context of gliomas, along with the development of combinatorial and potentially synergistic approaches with other established anti-cancer treatments or complementary immunotherapeutic modalities.